TRANSFORMING PARLIAMENTARY OVERSIGHT: EMERGING TRENDS IN PARLIAMENTARY OVERSIGHT AND DIGITAL GOVERNANCE (World Bulletin of Management and Law, 2026)
This article examines the prospects for improving parliamentary oversight exercised by the lower chamber, with a particular focus on institutional, legal, and technological dimensions. Special attention is given to the growing role of digital technologies and artificial intelligence in enhancing oversight capacities and facilitating public participation.